Online Practice Licensing for Health Workers in Sidoarjo District: Pendaftaran Lisensi Praktik Online untuk Tenaga Kesehatan di Kabupaten Sidoarjo - Ramadyanti, Mayyasya Tian; Choiriyah, Ilmi Usrotin (Indonesian Journal on Health Science and Medicine, 2025)
General Background: Digital transformation in public health administration is increasingly adopted to address bureaucratic complexity and service delays. Specific Background: The Sidoarjo District Health Office introduced the Online Practice License (SIP Online) system to manage health workers’ licensing amid growing demand and regulatory changes. Knowledge Gap: Limited empirical studies explain how local e-government licensing systems function in practice, particularly regarding target accuracy, socialization, goal attainment, and monitoring. Aims: This study examines the implementation of SIP Online using Budiani’s effectiveness indicators and identifies supporting and constraining factors. Results: Findings show that SIP Online has covered its intended users and shortened licensing time from 14 to 7 working days, while challenges persist in digital literacy among older health workers, irregular socialization, manual signature delays, and non-systematic evaluation. Novelty: The study provides a contextualized qualitative assessment of health licensing digitalization at the district level using an effectiveness framework rarely applied in this sector. Implications: Strengthening digital literacy, routine outreach, full process digitalization, and structured monitoring is crucial for sustaining accountable and adaptive public health services. Highlights: Licensing time was reduced through a fully online submission system. Digital literacy gaps remain a major operational constraint. Monitoring and evaluation require more systematic scheduling. Keywords: SIP Online; E-Government; Health Licensing; Public Service; Local Government